2013
DOI: 10.1128/mcb.00931-12
|View full text |Cite
|
Sign up to set email alerts
|

Hsp27 and F-Box Protein β-TrCP Promote Degradation of mRNA Decay Factor AUF1

Abstract: . It appears to perform this function by promoting degradation of the ARE-mRNA decay factor AUF1 by proteasomes. In this study, we examined the molecular mechanism linking Hsp27 phosphorylation to AUF1 degradation by proteasomes. AUF1 is a target of ␤-TrCP, the substrate recognition subunit of the E3 ubiquitin ligase Skp1-cullin-F-box protein complex, SCF ␤-TrCP . Depletion of ␤-TrCP stabilized AUF1. In contrast, overexpression of ␤-TrCP enhanced ubiquitination and degradation of AUF1 and led to stabilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 56 publications
1
23
2
Order By: Relevance
“…TTP destabilizes mRNA via its binding to AU-rich mRNA elements and is inactivated by phosphorylation [47]. Regarding Hsp27, it has recently been described as a regulator of the stability of mRNAs containing AREs [48]. Using the database "AREsite" [49], we found ARE presence in the 3'UTR of HB-EGF mRNA.…”
Section: Discussionmentioning
confidence: 97%
“…TTP destabilizes mRNA via its binding to AU-rich mRNA elements and is inactivated by phosphorylation [47]. Regarding Hsp27, it has recently been described as a regulator of the stability of mRNAs containing AREs [48]. Using the database "AREsite" [49], we found ARE presence in the 3'UTR of HB-EGF mRNA.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we showed that, similar to other ARE-BPs, TIS11/TTP proteins possess high turnover rates, which ensure the setting of rapid transitions in protein levels. However, while ARE-BPs such as AUF1 or HuR are targeted to degradation by ubiquitin-dependent mechanisms (16,17), we showed that TIS11/TTP proteins enter a ubiquitin-independent degradation-by-default pathway. The Drosophila dTIS11 protein and the mammalian TTP protein are both targeted for degradation by the same mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation was established between AUF1 degradation by the proteasome and ARE mRNA turnover (15). More recent data have also demonstrated that ubiquitination of AUF1 by the E3 ligase b-Trcp leads to its destruction by the proteasome and to the stabilization of its target mRNAs (16). HuR ubiquitination and subsequent proteasomal degradation upon heat shock has also been described (17).…”
mentioning
confidence: 84%
“…Interestingly, a ~70 kDa band that was serine–threonine‐phosphorylated in AUF1 immunoprecipitates might represent HSP70, recently identified as a substrate of AMPK (Schaffer et al ., 2015). It has been observed that phosphorylation of AUF1 has been reported to regulate AUF1 protein stability and binding to target mRNAs (Wilson et al ., 2003; Li et al ., 2013). AUF1 has also been implicated in regulating cellular senescence and also targets p16 INK4a , a potent regulator of senescence (Guo et al ., 2010; Pont et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%